The effect of the active carbonyl groups and residual acid on the ammonia adsorption over the acid-modified activated carbon - Li, Changming; Zhao, Shuying; Li, Ming; Yao, Zhiliang; Li, Yang; Zhu, Chuanqiang; Xu, Si-Min; Li, Junjie; Yu, Jian (Frontiers in Environmental Science, 2023)
The deep insight into the adsorption mechanism of ammonia (NH3) over acid-modified activated carbon will be of great significance to develop more efficient carbon materials for NH3 adsorption. In this work, a co-adsorption mechanism of NH3 and residual nitric acid (HNO3) on the active carboxyl site is proposed to elaborate the enhanced NH3 adsorption capacity over the acid-modified activated carbon based on both the experimental and density functional theory (DFT) results. The adsorption behaviors of NH3 over the different acid-modified activated carbon samples show that the activated carbon modified by 10 M HNO3 at 90 ºC possesses the best NH3 adsorption capacity (40 mg/g), and the residual HNO3 can be observed with the release of both NOx and NH3 during the heat treatment of the used HNO3-modified activated carbon. The multiple structural characterizations reveal that the activated carbon can be oxidized and etched by HNO3 with enriched pore structure and oxygen-containing functional groups, and acidic functional groups play a key role in the improved NH3 adsorption capacity. DFT calculations further display that the carboxyl functional group can strongly interplay with NH3 or HNO3 with the lowest adsorption energy (-0.66 eV and -0.79 eV, respectively), and the co-adsorption of NH3 and HNO3 around the carboxyl functional group forms a strong circular hydrogen-bond network among NO3−, NH4+ and carbonyl and further decreases the adsorption energy (-1.63 eV). The experimental and theoretical results together demonstrate that the oxidation and etching of activated carbon by acid enrich the active surface carboxyl functional groups, and the co-adsorption of NH3 with the residual HNO3 around the carboxyl functional group through the strong circular hydrogen-bond network accounts for the enhanced NH3 adsorption capacity of the acid-modified activated carbon.